Maximizing growth, flowering and corm productivity of gladiolus (Gladiolus spp.) varieties under integrated nutrient management system - DHAKAR, SUNITA; SWAROOP, K; SINGH, KANWARPAL; SHARMA, V K; SINGH, SURENDER; SINGH, NAVEEN (The Indian Journal of Agricultural Sciences, 2020)
Gladiolus (Gladiolus spp.) is widely used in flower arrangement, bouquets, bunches, baskets and indoor decorations. The growth, flower spikes, number of florests and yield of corms can be improved by adopting proper nutrient management practices. Research experiments were conducted to maximize growth, flowering and corm productivity of gladiolus varieties under integrated nutrient management system at the research farm of the Division of Floriculture & Landscaping, ICAR-Indian Agricultural Research Institute, New Delhi for two consecutive winter seasons during 2016-17 and 2017-18.Two gladiolus varieties as Pusa Red Valentine and Jyotsna in split-plot design were used and replicated three times with 12 treatment combinations. The study revealed that application of organic, inorganic and biofertilizers under INM system had showed significant effect on vegetative, flowering and yield of corm parameters. Significantly the maximum sprouting (98.75%) at 30 DAP, number of florets per spike (17.75) and the minimum days required for 50% blooming (100.10 days) were recorded with the application of 75% RDF+Vermicompost @ 10 t/ha + Azospirillum + PSB (T10), whereas maximum plant height (119.90 cm), spike length (108.92 cm), number of corm per plant(2.83) and number of cormels per plant (27.17 were observed with the application of 75% RDF + FYM @ 5 t/ha + Vermicompost @ 5 t/ha + Azospirillum + PSB (T11).The integrated nutrient management had also significantly recorded maximum vegetative, flowering and yield of corm parameter in variety Pusa Jyotsna as compared to Pusa Red Valentine variety during the study.